Analisis Kebijakan Dispensasi Kawin di Indonesia - Siswanto, Cecep Tedy (Universitas Proklamasi 45, 2025)
This study aims to examine and analyze in depth the marriage dispensation policy, which can be one of the factors in the occurrence of early marriage or child marriage in Indonesia. This research is a normative juridical research with a legislative approach and a conceptual approach. The main data source in this study is secondary data, consisting of primary legal materials and secondary legal materials. The results of the study show that changing the minimum age of marriage to 19 years does strengthen child protection. However, the opportunity for dispensation still weakens the effectiveness of these efforts. The conceptual problem in the definition of